ANALISIS KOMPARATIF KONSEP MAHMUD YUNUS TENTANG PENDIDIKAN ISLAM DAN PENDIDIKAN MODERN: SEBUAH STUDI RELEVANSI - Armedi, Rama (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This study aims to analyze the concept of modern education developed by Mahmud Yunus and its influence on improving the quality of Islamic education in Indonesia. Through a library research approach, this study collects and analyzes data from various sources such as books, articles, and internet sources. The results showed that Mahmud Yunus's reformist thinking had a significant influence in the development of modern Islamic educational institutions. Concepts such as subject integration, emphasis on faith and moral values, as well as the role of educators in character building, have proven relevant and can be integrated in contemporary Islamic education curricula. This research concludes that Mahmud Yunus' approach to Islamic education offers a new perspective that can answer the challenges of modern times and technological advances, while maintaining the essential values of Islamic education.